Genetic diversity and structure of the Australian flora. Issue 1 (13th November 2016) - Broadhurst, Linda; Breed, Martin; Lowe, Andrew; Bragg, Jason; Catullo, Renee; Coates, David; Encinas‐Viso, Francisco; Gellie, Nick; James, Elizabeth; Krauss, Siegfried; Potts, Brad; Rossetto, Maurizio; et al.
Abstract: Aim: To investigate the relationships between species attributes and genetic parameters in Australian plant species and to determine the associations in relation to predictions from population theory and previous global analyses. Location: Continent of Australia. Methods: We assembled a dataset of all known population genetic analyses of Australian plants based on neutral markers and catalogued them according to key species attributes, including range, abundance, range disjunction, biome and growth form; and genetic parameters, mean number of alleles per locus, observed and expected heterozygosity and population differentiation. We determined relationships between species attributes and genetic parameters using a maximum‐likelihood, multimodel inference approach. Results: We found many associations that were consistent with predictions. Species attributes with greatest effect on genetic diversity were range size, growth form, abundance and biome. The most important attributes influencing genetic differentiation were range disjunction and abundance. We found unexpected results in the effects of biome and growth form on genetic diversity, with greater diversity in the eastern biome of Australia, and lower diversity in shrubs compared to trees. Main conclusions: Our analysis of genetic diversity of Australian plants showed associations consistent with predictions based on population genetics theory, with strong effects of range size, abundance and growth form. We identified a striking effect of range disjunction on population genetic differentiation, an effect that has received little attention in the literature. We also found some notable differences to global predictions, which were most likely explained by confounding effects across variables. This highlights that caution is needed when extrapolating trends from global analyses to regional floras. Identifying associations between species attributes and patterns of genetic diversity enables broadscale predictions to facilitate the inclusion of genetic considerations into conservation decision‐making.